Prepubertal Presentation of Solitary Osteochondroma of Thoracic Spine – A Case Report - S Hameed (Malaysian Orthopaedic Journal, 2011)
An 11-year-old boy presented with an insidious onset, gradually progressive, painless swelling in upper back region that grew over the past 7 years. Spinal examination revealed a paraspinal globular mass on the left side at the level of the D1 to D4 vertebra. The swelling was bony hard in consistency, lobulated and fixed to underlying vertebra; there were no similar swellings on skeletal survey. Neurological and systemic examination was normal. Plain radiographs and computed tomography (CT) studies showed evidence of a lobulated, multiseptate, exophytic mass arising from the tip of the spinous process of D2 vetebra, with chondroid matrix calcification. Excision biopsy and resultant histopathological examination was suggestive of osteochondroma. Extant literature supports the origin of spinal osteochondroma from secondary ossification centres; thus, invariably, presentation of spinal exostosis occurs in the post-pubertal period. This case was unique in that the probable origin derived from a primary centre of ossification.